2014
DOI: 10.5604/20831862.1120936
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on How Do Elite Surfski Padllers Manage Their Effort and Hydration Pattern in the Heat

Abstract: To investigate thermal response, hydration behaviour and performance over flatwater kayaking races in tropical conditions (36.8°C and 68% rh). Five internationally-ranked subjects participated in the 2012 Surfski Ocean Racing World Cup in Guadeloupe to the “Ze Caribbean Race 2012” [i.e., a 35-km downwind race]. Core temperature (T°C) and heart rate (HR) were measured using portable telemetry units whereas water intake was deduced from backpacks absorption. The kayakers were asked to rate both their comfort sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 30 publications
4
7
3
Order By: Relevance
“…However, we did not demonstrate any correlation between the delta T c and the performance in the present paddlers, whereas we recently demonstrated that the IRP with the greatest increases in T c were the fastest during a 35-km race [9]. …”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…However, we did not demonstrate any correlation between the delta T c and the performance in the present paddlers, whereas we recently demonstrated that the IRP with the greatest increases in T c were the fastest during a 35-km race [9]. …”
Section: Discussioncontrasting
confidence: 86%
“…The performance expressed in relative units was not different from the performance noted in our previous study [ 9 ], indicating that ARP are paddling at a pace similar to the one used by IRP during a 35-km race. Similar mean HR was also observed between races.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…In their meta-analysis, Wegmann et al (2012) reported that pre-exercise immersion provided the best performances in situations of high thermal stress (high ambient temperature and/or long-duration exercise; Duffield and Marino, 2007). This was supported by our findings that the performances in tropical climate of both elite and average-level paddlers (Hue et al, 2014) were related to the increase in core temperature and that pre-race and end-race core temperatures were positively correlated, reinforcing the importance of beginning competition with a lower body temperature. The relationship between core temperature increase and performance was partially corroborated during a long trail race (Baillot et al, 2014) in which the best performers finished with the higher core temperatures.…”
Section: The Example Of Guadeloupe Experimentssupporting
confidence: 74%
“…The critical core temperature is dependent on factors (González-Alonso et al, 2008) like age, sex, hydration status, and most importantly training status and motivation. Baillot et al (2014) demonstrated that better trailers finished with higher water losses and core temperatures, and this was corroborated in high-level paddlers (Hue et al, 2014). Impaired thermoregulation processes after menthol + water immersion were noted by Rinaldi et al (2018).…”
Section: Limitationsmentioning
confidence: 74%